Novos materiais ativos na degradação de poluentes emergentes em meio aquoso: uso da espectrometria de massas com ionização paper spray na investigação de reações de oxidação em superfície - Susana Fátima Resende (2017)
The initial objective of this work was to synthesize composites(TiO2/SiO2-B2O3) with improved photocatalytic properties. For this purpose, some variables such as boron/titanium molar ratio and calcination temperature were evaluated towards the photodegradation of the dye indigo carmine in an aqueous medium. Hence,the degradation tests showed that the best photocatalyst was synthesized with a boron/titanium molar ratio of 1 and using a calcination temperature of 350 °C. This photocatalyst was able to remove 98 % of indigo carmine after 90 min of exposure to fluorescent lamps. The improved properties of this photocatalyst are probably related tothe interfaces (B2O3-TiO2-SiO2) present in its structure. This most efficient photocatalyst was also used for the removal of dacarbazine, cytarabine, tamoxifen and sildenafil in an aqueous medium, an unprecedented investigation. Excepting for cytarabine, all the other drugs were efficiently degraded. The use of ultra-high performance liquid chromatography coupled to mass spectrometry allowed for theby-products characterization and the proposal of degradation routes.A second objective of this work was to evaluate the efficiency, under visible light, of titanium-niobates photocatalysts, specifically Cu0.5Ti0.5NbO4 and Ni0.5Ti0.5NbO4, previously synthesized in our group. The influence of Cu2+ or Ni2+ as well as the presence of H2O2 on the photocatalytic efficiency of such materials towardsthe degradation of the dye indigo carmine in an aqueous medium were evaluated. The Cu0.5Ti0.5NbO4 photocatalyst showed higher activity under visible light, which was partly explained by its smaller gap. This photocatalyst degraded 95 % of indigo carmine in an aqueous solution after 150 min. The addition of H2O2 contributed significantly toincrease the activity of this photocatalyst. This reactant probably promoted the separation of the photogenerated charges at the photocatalyst surface. A third objective of this work was to apply the paper spray ionization mass spectrometry technique to monitor oxidation reactions taking place at the paper surface, specifically heterogeneous photocatalysis with TiO2 and Fenton/Fenton-like reactions.First, the results showed the superior activity of heterogeneous photocatalysis in comparison to photolysis to promote the on-surface degradation of the dye methylene blue. In sequence, Fenton reactions were remarkably more efficient than Fenton-like reactions in the on-surface degradation of sildenafil. The particular chemicalcharacteristics of Fe2+, such as oxidation potential, ionic stability and reaction kinetics were probably responsible for the higher efficiency of the Fenton system.